Comparative analysis of riboflavin and thiamine in raw and commercial honey - Slavica Sunarić; Jelena Živković; Ana Spasić; Jelena Lalić; Jelena Matejić (Czech Journal of Food Sciences, 2020)
The paper describes the determination of riboflavin and thiamine in the best-selling types of 13 raw and 8 commercial monofloral and multifloral honeys originating from Serbia. It was found that there is a difference in average riboflavin and thiamine content between raw and commercial honey, as well as between different honey floral varieties. The results showed that forest, meadow and oregano honey had a significantly higher content of both B vitamins compared to acacia, linden and lavender honey. On the other hand, a very low content of riboflavin and thiamine was found in honeydew honey. Among the commercial products, royal jelly was the richest in thiamine and riboflavin, followed by forest honey. In general, the quality of all of the commercial honey samples regarding these vitamins was lower than that of the raw domestic honeys.